2021
DOI: 10.29121/ijetmr.v8.i4.2021.918
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low Density Polyethylene Waste Filled With Palm Kernel Shell

Abstract: All over the world, polyethylene wastes has been found littered on the streets of most communities and states. Palm kernel shell (agricultural waste) constitutes dirt and environmental pollution. The aim of this research was to study the potentials of palm kernel shell (PKS) filler as reinforcement for low density polyethylene (LDPE) waste. LDPE-Palm kernel shell composites of varying ratio (100:0, 90:10, 80:20, 70:30, 60:40, 50:50) of LDPE to PKS respectively were produced using the compression moulding techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…An area of numerous applications of PKS derivatives is as reinforcement for composites. The suitability of PKS as a reinforcement in PKS-LDPE composite was investigated in the studies of Inegbedion et al (2021) and Nafu et al (2020). Results investigating the effect of PKS weight fraction in the study of Inegbedion et al (2021), showed an improvement of 76.06 % in stiffness, 55.07 % in ductility, 53.86 % in tensile strength and 24.33 % in hardness at 50 %, 10 %, 40 % and 50 % of PKS inclusion in the composite respectively.…”
Section: Use In Polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…An area of numerous applications of PKS derivatives is as reinforcement for composites. The suitability of PKS as a reinforcement in PKS-LDPE composite was investigated in the studies of Inegbedion et al (2021) and Nafu et al (2020). Results investigating the effect of PKS weight fraction in the study of Inegbedion et al (2021), showed an improvement of 76.06 % in stiffness, 55.07 % in ductility, 53.86 % in tensile strength and 24.33 % in hardness at 50 %, 10 %, 40 % and 50 % of PKS inclusion in the composite respectively.…”
Section: Use In Polymer Compositesmentioning
confidence: 99%
“…The suitability of PKS as a reinforcement in PKS-LDPE composite was investigated in the studies of Inegbedion et al (2021) and Nafu et al (2020). Results investigating the effect of PKS weight fraction in the study of Inegbedion et al (2021), showed an improvement of 76.06 % in stiffness, 55.07 % in ductility, 53.86 % in tensile strength and 24.33 % in hardness at 50 %, 10 %, 40 % and 50 % of PKS inclusion in the composite respectively. While studying the effect of PKS particle sizes, Nafu et al (2020), recorded maximum results in compressive stress of 0.75 MPa, flexural stress of 0.44 MPa, density of 0.852 g/cm 3 , and stiffness of 1754 MPa at 1 mm, 5 mm, 3 mm and 5 mm respectively.…”
Section: Use In Polymer Compositesmentioning
confidence: 99%